Oxidative Imbalance and Anxiety Disorders - Krolow, R.; Arcego, D. M.; Noschang, C.; Weis, S. N.; Dalmaz, C. (Current Neuropharmacology, 2014)
The oxidative imbalance appears to have an important role in anxiety development. Studies in both humans and animals have shown a strong correlation between anxiety and oxidative stress. In humans, for example, the increased malondialdehyde levels and discrepancies in antioxidant enzymes in erythrocytes have been observed. In animals, several studies also show that anxiety-like behavior is related to the oxidative imbalance. Moreover, anxiety-like behavior can be caused by pharmacological-induced oxidative stress. Studies using knockout or overexpression of antioxidant enzymes have shown a relationship between anxiety-like behavior and oxidative stress. Related factors of oxidative stress that could influence anxious behavior are revised, including impaired function of different mitochondrial proteins, inflammatory cytokines, and neurotrophic factors. It has been suggested that a therapy specifically focus in reducing reactive species production may have a beneficial effect in reducing anxiety. However, the neurobiological pathways underlying the effect of oxidative stress on anxiety symptoms are not fully comprehended. The challenge now is to identify the oxidative stress mechanisms likely to be involved in the induction of anxiety symptoms. Understanding these pathways could help to clarify the neurobiology of the anxiety disorder and provide tools for new discovery in therapies and preventive strategies.
Keywords: reactive species